1999
DOI: 10.1046/j.1471-4159.1999.721759.x
|View full text |Cite
|
Sign up to set email alerts
|

The Stimulation of Ketogenesis by Cannabinoids in Cultured Astrocytes Defines Carnitine Palmitoyltransferase I as a New Ceramide‐Activated Enzyme

Abstract: The effects of cannabinoids on ketogenesis in primary cultures of rat astrocytes were studied. Delta9-Tetrahydrocannabinol (THC), the major active component of marijuana, produced a malonyl-CoA-independent stimulation of carnitine palmitoyltransferase I (CPT-I) and ketogenesis from [14C]palmitate. The THC-induced stimulation of ketogenesis was mimicked by the synthetic cannabinoid HU-210 and was prevented by pertussis toxin and the CB1 cannabinoid receptor antagonist SR141716. Experiments performed with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 57 publications
1
57
0
1
Order By: Relevance
“…However, the signaling events involved in the cannabinoid-mediated induction of COX-2 expression remain to be established. Recent investigations indicate that several actions of cannabinoids, including inhibition of glioma cell growth (Galve-Roperh et al, 2000), effects on energy metabolism , and stimulation of ketogenesis (Blazquez et al, 1999) and glucose metabolism (Sanchez et al, 1998) are signaled through accumulation of the lipid second messenger ceramide. Ceramide is a membrane sphingolipid that can be generated by ceramide synthase, a key enzyme involved in de novo sphingolipid biosynthesis and in the reacylation of free sphingoid bases derived from sphingolipid turnover (Wang et al, 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the signaling events involved in the cannabinoid-mediated induction of COX-2 expression remain to be established. Recent investigations indicate that several actions of cannabinoids, including inhibition of glioma cell growth (Galve-Roperh et al, 2000), effects on energy metabolism , and stimulation of ketogenesis (Blazquez et al, 1999) and glucose metabolism (Sanchez et al, 1998) are signaled through accumulation of the lipid second messenger ceramide. Ceramide is a membrane sphingolipid that can be generated by ceramide synthase, a key enzyme involved in de novo sphingolipid biosynthesis and in the reacylation of free sphingoid bases derived from sphingolipid turnover (Wang et al, 1991).…”
mentioning
confidence: 99%
“…Whereas the rapid transient peak of ceramide induced by cannabinoids is linked to activation of SMase and has been implicated in the regulation of metabolic functions (Blazquez et al, 1999;Guzman and Sanchez, 1999), other actions of cannabinoids, including inhibition of glioma cell growth (Galve-Roperh et al, 2000), are associated with sustained ceramide generation. In the latter study, accumulation of de novo synthesized ceramide was observed after a latency of days.…”
mentioning
confidence: 99%
“…Le C75, par exemple, active également CPT1 in vitro et n'agit peut-être pas uniquement via l'inhibition de la FA. L'activation de l'AMPK par l'AICAR conduit aussi à une augmentation de la synthèse des corps cétoniques par les astrocytes [32], ce qui peut aussi induire une baisse de la prise alimentaire. Ainsi, même si le métabolisme des acides gras peut être nécessaire pour relayer leur effet, on peut aussi envisager des mécanismes d'action indépendants.…”
Section: Mécanismes Moléculaires Relayant L'effet Des Acides Grasunclassified
“…30c Ceramide then causes activation of the Raf-1/MAP kinase cascade 36 and also carnitine palmitoyltransferase I in mitochondrial membranes to stimulate ketogenesis and fatty acid oxidation. 37 This elevation in levels of intracellular ceramide have also been suggested to be one of the possible factors responsible for the apoptotic effects of cannabinoids seen on glioblastoma cells. 38 The CB2 cannabinoid receptor, also referred to as the peripheral cannabinoid receptor, is a 41 kDa, 360 amino acid polypeptide that is predominantly expressed in the immune system.…”
Section: Cannabinoid Receptorsmentioning
confidence: 99%